FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA SISTEM INFORMASI AKUNTANSI PADA BANK SWASTA DI WILAYAH MANADO - Prayanthi, Ika (JBE (Journal of Business and Economics); Volume 12 No.2, 2013 JBE UNKLAB, 2013)
The objective of this research is to examine influence factors toward performance of accounting information sistem (AIS). Performance of AIS is measured by system use and satisfaction of AIS users. This research focused on several factors such as user involvement, personal capability engineering, organization size, top management support, formalization of information system, user training and education program, there is a steering committee, and dependence or independence of the information system department. The research data are obtained by means of questionnaire directly to the 80 respondents of four private bank in Manado. The analysis method of this research using simple regression analysis and independent sample T test. The result of simple regression test shows that only user involvement and top management support affect significantly to the user’s satisfaction. Despitefully, user involvement, personal capability engineering, top management support and formalization of information system also affect significantly to the usage of system.  Meanwhile, on difference test using compare mean independent sample T test is to be found evidence that there is a different of AIS performance in line with wether or not a steering commitee, the independence or dependence of the IS department user training and education program (only usage of system).